1622WQ: A web-based application to increase farmer awareness of the impact of agriculture on water quality. (October 2020) - Vilas, Maria P.; Thorburn, Peter J.; Fielke, Simon; Webster, Tony; Mooij, Martijn; Biggs, Jody S.; Zhang, Yi-Fan; Adham, Adam; Davis, Aaron; Dungan, Bertrand; Butler, Roger; Fitch, Peter
Abstract: Intensive agricultural practices represent a major threat to aquatic ecosystems because they impair water quality. However, this can be ameliorated by farmers improving crop management provided they are aware of their contribution to declining water quality. Water quality information systems can increase farmer awareness, but most were developed to assess water quality targets set in regulations rather than inform farmers. We developed the 1622WQ application using user-centred design principles to provide farmers with real-time information on nitrate and other contextual variables in their local creeks and rivers. The design process identified barriers to uptake of the application such as: (a) limited internet connection; (b) poor data quality; and (c) operational issues. Once these barriers were addressed, there was substantial uptake. Nevertheless, providing real-time information to farmers is only part of the solution due to legacy issues caused by a digital divide between traditional industries and those that are digitally enabled. Highlights: 1622WQ is an app that democratises water quality monitoring data. Added contextual information makes the water quality data more relevant to farmers. We increased uptake through social science and human-centred design. Transdisciplinary work was important to achieve impact of the technology.